2008
DOI: 10.1152/ajpgi.90285.2008
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB2 receptors in the enteric nervous system modulate gastrointestinal contractility in lipopolysaccharide-treated rats

Abstract: Enhanced intestinal transit due to lipopolysaccharide (LPS) is reversed by cannabinoid (CB)2 receptor agonists in vivo, but the site and mechanism of action are unknown. We have tested the hypothesis that CB2 receptors are expressed in the enteric nervous system and are activated in pathophysiological conditions. Tissues from either saline- or LPS-treated (2 h; 65 microg/kg ip) rats were processed for RT-PCR, Western blotting, and immunohistochemistry or were mounted in organ baths where electrical field stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
134
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(151 citation statements)
references
References 49 publications
15
134
1
1
Order By: Relevance
“…Indeed, low doses of LPS have been reported to enhance intestinal motility through mechanisms implicating the enteric nervous system and the modulation of the production of several neuroimmune mediators (including IL-1, cyclooxygenase, and constitutive nitric oxide synthase) in mice and rats. [43][44][45] Although not directly addressed, similar mechanisms might be contributing to the changes observed in the present study, with direct effects of LPS on local neuroimmune responses leading to alterations in smooth muscle contractility.…”
Section: Discussionmentioning
confidence: 68%
“…Indeed, low doses of LPS have been reported to enhance intestinal motility through mechanisms implicating the enteric nervous system and the modulation of the production of several neuroimmune mediators (including IL-1, cyclooxygenase, and constitutive nitric oxide synthase) in mice and rats. [43][44][45] Although not directly addressed, similar mechanisms might be contributing to the changes observed in the present study, with direct effects of LPS on local neuroimmune responses leading to alterations in smooth muscle contractility.…”
Section: Discussionmentioning
confidence: 68%
“…Recent studies have described the presence of the CB2 receptor mRNA and the CB2 receptor protein in the rat ileal myenteric plexus (Storr et al, 2002;Duncan et al, 2008). However, the ability of cannabinoid receptor agonists to delay small intestinal transit of the rat in vivo through this receptor has been reported to occur only after inflammation of the small intestine with the bacterial endotoxin lipopolysaccharide (Mathison et al, 2004), and not other inflammatory agents (Izzo et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In the rat ileum, the mRNAs of both cannabinoid receptors and their expression have been both identified and mapped in the myenteric plexus Valenti et al, 2005;Duncan et al, 2008). Furthermore, a number of endogenous cannabinoid ligands, exemplified by arachidonylethanolamide (AEA) and 2-arachidonylglycerol (2-AG), (Gomez et al, 2002;Mascolo et al, 2002;Izzo et al, 2003;Fegley et al, 2005;Valenti et al, 2005), along with the mechanisms for their enzymatic inactivation (Katayama et al, 1997), have been shown to be present in the rat ileum.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal conditions, CB 1 mediates the effects of cannabinoids on motility; however, in inflammatory states both CB 1 and CB 2 receptor activation may reduce inflammation-induced hypermotility. For instance, in lipopolysaccharide (LPS)-induced intestinal inflammation, hypermotility was normalized following CB 2 (but not CB 1 ) activation [19,20], whereas in croton oil-induced hypermotility CB 2 antagonism did not reverse the effect of the cannabinoid agonist CP55,940 [8]. In another study of LPS-induced inflammation, the FAAH inhibitor AM3506 normalized hypermotility in a CB 1 -and CB 2 -dependent manner, whereas colonic propulsion was CB 1 -dependent [21].…”
Section: Role Of the Ecs In Gut Homeostasismentioning
confidence: 99%